Evaluation of the Outcome of Ilizarov External Fixator in Tibial Non-union - Badar Uddin, K M; Khan, Md Rukanuddawla; Chakraborty, Swarupananda; Nath, Asho Tosh; Mahmood, Sheikh Kawsar; Mazher Ali, Khandoker Muhammud (Medicine Today, 2025)
Introduction: Tibial non-union ranges from 2-10% of all tibia fractures. Infection, deformity, shortening, bone loss, joint stiffness and disability complicate the non-union. Ilizarov method addresses all the above problems simultaneously and offers a panacea for infected non-unions. This study was conducted to evaluate the impact on overall outcome of ilizarov external fixator in tibial non- union. Materials and Methods: This prospective study was carried out at the Department of Orthopedic Surgery at Chittagong Medical College Hospital, Chittagong from June 25, 2018 to June 24, 2019. Results were analyzed according to ASAMI scoring system at the end of study by using windows based computer software devised with SPSS-23. Result: Out of 12 cases, 11cases (91.7%) were male and only 1 case (8.3%) was female. Mean (±SD) age was 27.58±5.62 years. Excellent bony result was obtained in 16.7%, good in 50%, fair in 16.7% and poor in 16.7% of patients. Two (16.7%) patients had excellent, 4 (33.3%) patients had good, 3 (25%) patients had fair and 3 (25%) patient had poor functional outcome. Conclusion: Treatment of non-unions of Tibia with Ilizarov ring fixation is effective. However, larger randomized control trial is required to generate more valuable conclusion. Medicine Today 2025, Vol.37 (1): 119-122